Effect of the Armonia Program on performance and academic stress in higher education students in Lima - Llanos Ballardo, Milagros Lucía (2022)
This research evaluated the effect of the Armonía program, based on mindfulness, on academic performance and academic stress in students of a higher education institution in Lima, through 8 sessions of approximately 1 hour and 30 minutes, for 8 weeks. A quasi-experimental design with pre and postest was used, with two groups (experimental and control), both with 25 randomly assigned participants, who had a mean age of 19.82 years. For the measurement of stress, the SISCO SV-21 Inventory was used and for academic performance, the grades of the first and second partials, completed by the teachers, were used. It was found that there are statistically significant effects in favor of stress reduction in general explained by the program with a large effect size (d = 1.18; p < .01), as well as for its stressor dimensions (d = 1.39; p < .01), symptoms (d = 2.88; p < .01) and coping strategies (d = -3.16; p < .01); Likewise, statistically significant effects were determined in favor of the increase in global academic performance explained by the program with a medium effect size (d = -0.42; p = .04). It is concluded that there is sufficient evidence to determine the effectiveness of the program in reducing stress; however, despite having a certain effect on academic performance in general, more research is needed to determine its influence on this variable and its components.